2016
DOI: 10.1007/s10694-016-0572-8
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Thermal Characteristics of a Circular Fusible-Type Sprinkler Using the Energy Transport Equation

Abstract: In this study, we investigate the thermal characteristics of a circular fusible-type sprinkler. Analytic solutions regarding the radial-temperature distribution are obtained by using the energy-transport equation for the heat-responsive element of the sprinkler. When solving the equation, the fitted curves of the measured temperatures derived from the previous correlation of the heat-transfer coefficient are used as the boundary conditions at the element surface. To verify the accuracy of the present approach,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
2
0
1
Order By: Relevance
“…They found that the modelled bulb temperature evolution matched the experimental curve closely in the case of the plunge tests, but they detected considerable differences when using ceiling jet temperature and velocity data from compartment fire experiments, especially for fast-growing fires. A more sophisticated model for sprinkler link temperature was presented by You et al [10]. They proposed to include radial dependence in the temperature inside the link and provided analytic and numerical solutions for the resulting equations.…”
Section: The Rti Modelmentioning
confidence: 99%
“…They found that the modelled bulb temperature evolution matched the experimental curve closely in the case of the plunge tests, but they detected considerable differences when using ceiling jet temperature and velocity data from compartment fire experiments, especially for fast-growing fires. A more sophisticated model for sprinkler link temperature was presented by You et al [10]. They proposed to include radial dependence in the temperature inside the link and provided analytic and numerical solutions for the resulting equations.…”
Section: The Rti Modelmentioning
confidence: 99%
“…등방성을 갖고 주위로 열손실이 없는 상태를 가정하여 유도 된 관계식이기 때문에 스프링클러와 같이 배관 또는 작동 유체인 물과 접합되어 설치된 경우 접합부로 열 손실일 발 생하여 작동 시간이 지연되는 현상이 나타날 수 있다 (1,8,9) . 스프링클러의 감열부 열손실에 관한 연구로 Heskestad (8) 은 기류의 온도와 속도를 일정하게 증가시키면서 감열부의 반응성을 고려한 반복시험에 의해서 수정된 반응시간지수 (RTIv)를 제시하였으며, 손실인자인 C-factor를 산출하기 위 한 방안은 현재 FM Class 2000의 스프링클러 시험기준에 적 용하고 있다 (6) .…”
unclassified
“…In both cases, the systems were capable of controlling the fire and preventing structural damage, however the water mist configuration tested performed better, especially when an additive was used. Jun et al has also proposed a more detailed energy transport equation for the activation of circular fusible-type sprinklers which may aid in research and development of new designs [12]. Of course, the missing link in all of these technologies is notification of occupants that there is a fire so that they can evacuate in a timely manner.…”
mentioning
confidence: 99%